2018
DOI: 10.12691/ajnr-6-1-3
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Nursing Students Engagement in Their Learning Environment

Abstract: Student engagement is seen more than to just involve student during organization time its meaning has become more vast than previously assumed. Now, it is viewed by diverse aspects not a one aspect consider enough to define engagement. Student's emotional, cognitive and behavioral participation in their learning environment is considered as true engagement. It is not also helpful to engage student in course material but also help students to get better outcome. Nursing student engagement is essential in this r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…On the contrary, Abdul Sattar, Kouar and Gillani (2018) 24 in a cross sectional study among 135 undergraduate students reported no significant relationship between student engagement and self-reported cumulative GPA. Abdul Sattar et al (2018) 24 study favored that student who hold low GPA try to engage more in their learning environment to get better results in future.…”
Section: Literature Reviewmentioning
confidence: 92%
See 1 more Smart Citation
“…On the contrary, Abdul Sattar, Kouar and Gillani (2018) 24 in a cross sectional study among 135 undergraduate students reported no significant relationship between student engagement and self-reported cumulative GPA. Abdul Sattar et al (2018) 24 study favored that student who hold low GPA try to engage more in their learning environment to get better results in future.…”
Section: Literature Reviewmentioning
confidence: 92%
“…On the contrary, Abdul Sattar, Kouar and Gillani (2018) 24 in a cross sectional study among 135 undergraduate students reported no significant relationship between student engagement and self-reported cumulative GPA. Abdul Sattar et al (2018) 24 study favored that student who hold low GPA try to engage more in their learning environment to get better results in future. On same vein, Ghiyasvandian, Shahsavari, Kazemnejad, Goodarzi and Razavi (2019) 25 found that there was also a significant, but weak, relationship between the engagement to learning and academic achievement in the interactive classroom management.…”
Section: Literature Reviewmentioning
confidence: 92%
“…Student engagement is essential in both classroom and clinical practice settings for nursing students. A research study of Sattar et al, (2018) showed that three domains of student engagement (Hudsonm 2015) (Vollet, 2017) i.e. meaningful process (3.75), participation (3.35) and attention focus (3.25) had a high average score).…”
Section: Discussionmentioning
confidence: 99%
“…The three subdomains also had a positive correlation in which one subdomain increased the other subdomains. All domains of student engagement were critical to student nurses in classrooms as well as in clinical practice setting (Abdul, 2018). The engagement of students in the clinical environment is related to the diversity of patient status, conditions which enable students learning various cases, and mentor support and care improve the quality of being 'engaged' between student nurses and patients by creating decisions in collaboration(.…”
Section: Discussionmentioning
confidence: 99%
“…It was affiliated to the higher education ministry High-level "if the percent ≥ 75%,equal (88-117), moderate level, "from 60% to less than 75% equal (71-87) and Low level "< 60 %" equal (39-70) 2 nd tool: Nursing Students' Engagement Questionnaire. It was developed by the researchers after reviewing related literature (Abdelhalim, et al, 2022& Abdul Sattar , et al, (2018 and aimed to assess the levels of nursing students' engagement in their learning environment. It consisted of (31 items) categorized as follows; academic engagement (10 items), cognitive engagement (12 items), behavioral engagement (9 items).…”
Section: Settingmentioning
confidence: 99%